If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -1y = 11 Add '-11' to each side of the equation. 11 + -11 + -1y = 11 + -11 Combine like terms: 11 + -11 = 0 0 + -1y = 11 + -11 -1y = 11 + -11 Combine like terms: 11 + -11 = 0 -1y = 0 Solving -1y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-1'. y = 0 Simplifying y = 0
| -9-7x= | | 8x-3=87-2x | | 0.07z=-0.72-5(0.3z-1.4) | | m/7-9=8 | | 9a+12=7a+9 | | 0-y=111 | | 250+t=141 | | 56ty-11=247 | | 200-3y-4x=0 | | 8.1-0.6t=7.2 | | 7(2x+10)=6x+26+6x+4 | | a-95=25 | | gcf=42x+28y | | b-5+0.2b=-0.2 | | -8(7)+y=4 | | x^5-3x^4-x^3+3x^2=f(x) | | 2/3+3x+1/4=5/3 | | -8(3)+y=4 | | 3.2x-0.88+1.2=0 | | -8(-2)+y=4 | | 2(5x+4)+2=60 | | 4g-8=-20 | | X*2+5x+3=0 | | 2+3(5+5v)=62 | | 42x+28y=gcf | | -2(3y-4)-y=-4(y-2) | | 3(3x+2)=6(2x-3) | | 9x+3=7x-19 | | 2+15+15v=62 | | 40r^2-35r+16r-14=0 | | 50m+42750=42675-175m | | 4(2x-7)=3(x-1) |